Light and scanning electron microscopy of Datura stramonium L. extract and its biological applications. Issue 8 (12th May 2022) - Rehman, Shafiq Ur; Ullah, Nadeem; Jaffer, Mehwish; Zaidi, Riffat; Anwar, Hina
Abstract: The study deals with the LM and SEM (light microscopy and scanning electron microscopy) of Datura stramonium L. extract and to evaluate its phytochemical, antimicrobial, and antioxidant activities. The plant sample collected from different Lahore region was dried under shade. The plant extract was prepared using different solvents (n‐hexane, chloroform, ethyl acetate, and methanol). Phytochemical screening performed qualitatively for alkaloids, carbohydrates, flavonoids, saponins, and tannins. Radical scavenging potential of plant extracts was estimated and ethyl acetate extract exhibited maximum percentage scavenging ability of 92.2 ± 0.09. Total antioxidant capacity of different extracts was measured by phosphomolybdate method. The ethyl acetate and methanolic extracts showed maximum values of 72.3 ± 0.08% and 79 ± 0.15% with respect to gallic acid. Total phenolic contents were determined through Folin‐Ciocalteau method and highest value of 495.2 ± 3.4 was obtained by methanolic extract. DPPH‐TLC autography was used for the visual detection of antioxidant compounds in different plant extracts. Antibacterial activity of plant extract was measured by disc diffusion method against microorganisms named Bacillus licheniformis, Bacillus subtilis (Gram positive), and Salmonella typhimurium, and Proteus mirabilis (Gram negative). Because of the vast medicinal importance of D. stramonium L. it would be beneficial to study LM and SEM for correct identification of plant and to determine phytochemicals. Research Highlights: LM and SEM (light microscopy and scanning electron microscopy) of Datura stramonium L. was studied for the exact identification of plant. To evaluate the biological activities of pharmaceutically important plant. Antioxidant and antimicrobial activity were determined. D. stramonium L. proved to be medicinally important plant. scheme of experimental work: